Fusarium Endophthalmitis, Unusual and Challenging Infection in an Acute Leukemia Patient. (13th March 2018) - Baysal, Mehmet; Umit, Elif; Boz, İbrahim Bekir; Kırkızlar, Onur; Demir, Muzaffer
Abstract : Invasive fungal infections bring serious mortality and morbidity during the treatment of acute myeloid leukemia. Especially, mold infections are challenging, and each case is unique in feature. These cases are usually fatal, and there is no consensus regarding optimal treatment. AML patients receive antifungal prophylaxis and may further require IFI (invasive fungal infection) treatments, but fusarium mold infections are often unrecognized and could be overlooked. In this case report, we try to emphasize the importance of this infection with a high-risk AML patient.